2013
DOI: 10.3916/c41-2013-10
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of research on women and advertising: Differences in print and audiovisual media

Abstract: Análisis bibliométrico de la investigación sobre mujer y publicidad: diferencias en medios impresos y audiovisuales❖ Marián Navarro-Beltrá is FPI Researcher in the Communication and Social Psychology Department of the Faculty of Economic and Business Sciences at the University of Alicante in Spain (marian.navarro@ua.es). ❖ Dr. Marta Martín Llaguno is Senior Lecturer in the ABSTRACTThe media in general, and advertising in particular, are considered as important agents of socialization, including gender-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…Their study found that articles originating from Mainland China elicited the most citations, followed by those from Taiwan, Hong Kong, and Macau, respectively. Other contemporary bibliometrics research has examined a variety of topics such as social capital (Chul-joo & Dongyoung, 2016), virtual media (Correia et al, 2014), video gaming (White, 2011), and gender and media (Navarro & Martín, 2013).…”
Section: Citation Analysis In Communication Researchmentioning
confidence: 99%
“…Their study found that articles originating from Mainland China elicited the most citations, followed by those from Taiwan, Hong Kong, and Macau, respectively. Other contemporary bibliometrics research has examined a variety of topics such as social capital (Chul-joo & Dongyoung, 2016), virtual media (Correia et al, 2014), video gaming (White, 2011), and gender and media (Navarro & Martín, 2013).…”
Section: Citation Analysis In Communication Researchmentioning
confidence: 99%
“…En relación con la televisión como concepto general, un estudio de Piñeiro-Naval & Morais (2019) confirma que la televisión es uno de los objetos de estudio recurrentes de los académicos de España y América Latina. En esa línea de trabajo, se encontraron bibliometrías de caracterización de tesis doctorales sobre la televisión (Repiso, Torres & Delgado, 2011), el emplazamiento de producto en sus contenidos (Guo et al, 2019), el perfil del desarrollo académico de la literatura de televisión interactiva (Chen, Tsaih & Chou, 2009), el rol de la mujer (Navarro & Martín, 2013)and advertising in particular, are considered as important agents of socialization, including genderrelated issues. Thus the legislator has focused on the regulation of the images of women and men in advertisements.…”
Section: Introductionunclassified
“…When the literature is examined, studies including bibliometric analysis in varying fields are encountered such as communication (Fombona, Pascual-Sevillana & Gonzalez-Videgaray, 2017;Navarro-Beltrá & Martín-Llaguno, 2013), administration (Avelar, da Siva-Oliveria & da Silva Pereira, 2019;Berbegal-Mirabent, Alegre & Ribeiro-Soriano, 2018), linguistics (Lei & Liu, 2019, Yilmaz, Topu & Tulgar Takkaç, 2019, philosophy (Fernandez & Sundström, 2011), music (Diaz & Silveira, 2014;Hancock, 2015), sports (Ciomaga, 2015) and social studies (Lara-Aparicio, Mayorga-Vega & Lopez-Fernandez, 2019;Pérez-Gutiérrez & Gutierrez-Garcia, 2015;Porto-Maciel, Araldi & Andrade, 2019) and also many others that are not included here.…”
Section: Introductionmentioning
confidence: 99%